Saúde mental: a roda viva da política pública do estado do Pará - MOTA, Josie Pereira da (Universidade Federal do Pará, 2012)
Over the past decades several countries, including Brazil have implemented policies for mental health care, based on the common central element of change in care from hospital to the community, aiming at continuity of care and comprehensive care, a process is usually called Psychiatric Reform. Trying to understand "What is the model of care applied in Pará between 2007 and 2010, the traditional mental hospital or psychiatric reform and what policy outcomes in terms of effectiveness?". This survey was conducted from a literature review on psychiatric reform processes in various countries in Europe, Latin America without losing sight of the specificities of Brazil and Para an analysis of the role of the state, social policies, among them the public policy of Health and Health System in addition to document analysis and interviews with the performers policies. As results were observed advances in mental health policy between 2007 and 2010, such as increased (96%) in the number of services, albeit with the effectiveness questioned by both management and the social movement, and establishing a communication channel between management and social movement through management councils, internal ombudsmen and various training events. On the other hand, the structural problems persist, according to the analysis performed are related to the political and economic context experienced by Brazil's deepening social inequality and denial of social, economic, cultural and environmental rights established in the 1988 Constitution. It is evident, therefore, the consolidation of the neoliberal globalization process, with actions aimed at economic stability and targeting of social policies. As an alternative to this situation the author presents the view that SUS is a system under construction and that the challenge posed in the present situation which has the aim of overcoming deep social inequalities through a mass movement to incorporate the proposals for overcoming the crisis and move into concrete proposals.